The Effect of Social Media Advertising Features on Purchase Intention Mediated By Brand Engagement on Lenovo Laptops - Wijaya, Jonathan Adriel; Susilawaty, Lilis (Business Management Journal, 2023)
The number of social media users always increases every year, realizing the potential of social media as a media for conducting marketing activities. This study aims to investigate the effect of social media advertising features (interactivity, perceived relevance, informativeness, and entertainment) on brand engagement, the effect of brand engagement on purchase intention, and the effect of social media advertising features on purchase intention mediated by brand engagement on Lenovo laptops in Indonesia. This research is descriptive research with a quantitative approach. The samples contained in this study amounted to 160 respondents, The sampling method used is non-probability sampling with convenience sampling technique. The analytical method used is PLS-SEM using Smart-PLS 3. The results of this study found that brand engagement has a significant effect on purchase intention, social media advertising features (interactivity and informativeness) have a significant effect on brand engagement. It was also found that social media advertising features (interactivity and informativeness) have a significant effect on purchase intention which is mediated by brand engagement. However, on social media advertising features (perceived relevance and entertainment) have insignificant effect on brand engagement. Then social media advertising features (perceived relevance and entertainment) have insignificant effect on purchase intention mediated by brand engagement.